Delayed absorbable synthetic plug (GORE® BIO‐A®) for the treatment of fistula‐in‐ano: a systematic review. (January 2016) - Narang, S. K.; Jones, C.; Alam, N. N.; Daniels, I. R.; Smart, N. J.
Abstract: Aim: Recent advances in the treatment of fistula‐in‐ano have focused on surgical techniques that preserve sphincter integrity. Plugs that obliterate the lumen of the fistula track have been proposed as one such method, and may be derived from biological or delayed absorbable synthetic materials. Biological plugs have highly variable results and have not been widely adopted. The aim of this systematic review was to assess the effectiveness and safety of a delayed absorbable synthetic plug (GORE® BIO‐A®) for treatment of anal fistula. Method: A systematic review of all literature in the English language relevant to the use of a plug to treat anal fistula and published between 1 January 2008 and 15 February 2015 was carried out by searching MEDLINE, EMBASE and the Cochrane Library of Systematic Reviews/Controlled Trials for relevant literature. Relevant articles were identified, quality assessed using the methodological index for nonrandomized studies criteria and data were extracted by two independent researchers (SKN and NNA). The identified articles were assessed with regard to fistula healing rate, duration of follow‐up and complication rates related to the use of delayed absorbable synthetic fistula plugs. Results: Twenty six potential articles were identified from the literature search. Using the predefined inclusion and exclusion criteria, six were included in the final analysis, data extraction and data synthesis. Of these included in the review only three were prospective in design. Complete data were available for 187 of the 221 patients who underwent this treatment. The age of the participants ranged from 19 to 82 years. The fistula healing rates were reported to be between 15.8% and 72.7% at a follow‐up ranging between 2 and 19 months. Early or delayed plug extrusion occurred in 16 (8.5%) of the 187 patients. Deterioration in continence was reported in 11 (5.8%) of 187 patients. Conclusion: There are insufficient high‐quality data on the delayed absorbable synthetic (GORE® BIO‐A®) fistula plug to draw meaningful conclusions regarding its effectiveness. It does, however, appear to be a simple and safe technique associated with low complication rates and a minor deterioration in continence in a few cases.